2014
DOI: 10.1167/iovs.13-13454
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Adaptive Optics Retinal Imaging of Cellular Structure in Choroideremia

Abstract: The data support the RPE being one primary site of degeneration in patients with choroideremia. Photoreceptors also may degenerate independently. High resolution imaging, particularly AOSLO in combination with OCT, allows single cell analysis of disease in choroideremia. These modalities promise to be useful in monitoring disease progression, and in documenting the efficacy of gene and cell-based therapies for choroideremia and other diseases as these therapies emerge. (ClinicalTrials.gov number, NCT01866371.). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
109
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 40 publications
6
109
0
3
Order By: Relevance
“…It is also supported by recent structural characterization of choroideremia male and female carriers using adaptive optics scanning light ophthalmoscopy. 5 In summary, these data suggest that RPE degeneration and reduced retinal function in choroideremia are related nonlinearly. Clinically, we recommend a multimodal, deep phenotyping approach to all choroideremia carriers, including the use of microperimetry and AF.…”
Section: Correlation Of Retinal Structure and Function In Choroideremmentioning
confidence: 78%
“…It is also supported by recent structural characterization of choroideremia male and female carriers using adaptive optics scanning light ophthalmoscopy. 5 In summary, these data suggest that RPE degeneration and reduced retinal function in choroideremia are related nonlinearly. Clinically, we recommend a multimodal, deep phenotyping approach to all choroideremia carriers, including the use of microperimetry and AF.…”
Section: Correlation Of Retinal Structure and Function In Choroideremmentioning
confidence: 78%
“…[12, 17–26] Indeed, confocal AOSLO has recently been used to document lack of cone reflectivity in the ORTS found in age-related macular degeneration. [27] In choroideremia, AOSLO imaging has uncovered novel pathologic features including bubble-like lesions that appear to co-localize to structures in the choroid visualized by SD-OCT[26] and yielded results suggesting a primary RPE degeneration with subsequent loss of photoreceptors and choroid.…”
Section: Introductionmentioning
confidence: 99%
“…[12, 17–26] Indeed, confocal AOSLO has recently been used to document lack of cone reflectivity in the ORTS found in age-related macular degeneration. [27] In choroideremia, AOSLO imaging has uncovered novel pathologic features including bubble-like lesions that appear to co-localize to structures in the choroid visualized by SD-OCT[26] and yielded results suggesting a primary RPE degeneration with subsequent loss of photoreceptors and choroid. [12, 26] Recent work by Morgan et al showed an abrupt decline in confocal AOSLO photoreceptor reflectivity in areas of RPE degeneration[26], while SD-OCT imaging revealed interdigitation zone (IZ, thought to represent the junction of photoreceptors and RPE) dropout and RPE thinning prior to disruptions in the overlying EZ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now with commercially available AO imaging systems, such as the flood-illuminated rtx1 from Imagine Eyes (Orsay, France), the Compact AO retinal imager from Physical Sciences, Inc. (Andover, MA, USA), and an AO scanning laser ophthalmoscope from Canon, Inc. (Tokyo, Japan), AO-aided imaging is becoming a more clinically viable tool for assessing retinal disease. [27][28][29][30] We used the rtx1 flood-illuminated AO camera from Imagine Eyes to develop a protocol for imaging and sampling cone density from a large macular area in healthy subjects. Previous studies have used the rtx1 to examine retinal diseases, 12,21,22,[31][32][33][34][35][36] study the healthy eye, [37][38][39][40] and optimize AO imaging parameters.…”
mentioning
confidence: 99%